First-principle calculations of the structural, vibrational, mechanical, electronic, and optical properties of ε-O8 under pressure - Bao, Shi-Yuan; Hong, Dan; Lu, Yi-Chen; Liu, Qi-Jun; Liu, Zheng-Tang; Zhang, Jian-Qiong (Journal of molecular modeling, 2022)
The vibrational, mechanical, electronic, and optical properties of the ε -O 8 phase in the pressure range of 11.4–70 GPa were studied by the first-principle calculation method. The phonon dispersion curves have a tiny virtual frequency at 60 GPa, which indicates that ε -O 8 is dynamically unstable at 60 GPa. However, the 3-BM EOS demonstrates that the unit cell is stable up to 70 GPa. It has been shown that ε -O 8 remains ductile within the whole applied pressure range. Concurrently, we calculated the variation of the band gap of ε -O 8 in the pressure range of 11.4–70 GPa. The results show that the band gap of ε -O 8 decreases with increasing pressure. Notably, the band gap disappears within the range of 50–60 GPa, which reveals that the metallic phase transition occurs within this pressure range.